Medical Negligence Litigation in Malaysia: Trends and Challenges - Jahn Kassim, Puteri Nemie (2012)
Litigation has never been a haven for neither the doctor nor the patient. Although at present, Malaysia is not experiencing the kind of “malpractice crisis”, there is certainly a rise in the number of negligence claims and the size of awards. These factors are sufficient to cause alarm for future implications and generate serious thoughts for reform of the present system. The deficiencies of the present tort system in handling medical negligence claims have been apparent for a number of years. Most of the criticism is directed at whether the action of negligence is a suitable means to compensate victims of medical injury. For a medical negligence claim to succeed, the patient has to overcome the substantive law as well as the procedural law inherent in the tort system. Often, both the substantive and the procedural law tend to work against the interest of the patient. Furthermore, the present system seems ill equipped to provide non-legal remedies such as explanation and investigation of events leading to the mishap. There is a cry for reform within the tort system itself and also for the implementation of alternatives to the fault-based system such as a no-fault compensation scheme and methods of alternative dispute resolution. However, incremental changes such as adopting measures to complement the tort system should be introduced to promote efficiency, predictability and accountability.